Creative adolescent experiences of education and mental health during COVID‐19: A qualitative study. Issue 2 (8th May 2022) - Zaeske, Lauren M.; Harris, Taylor P.; Williams, Amanda; Scheibel, Gretchen; Long, Haiying; Kerr, Barbara A.
Abstract: This qualitative study investigated creative adolescent perceptions of their educational and mental health experiences during the coronavirus disease 2019 (COVID‐19) pandemic. Participants were 25 English‐speaking adolescents from the Midwest in the United States. They were identified as creative by their teachers according to known creative profiles. Participants attended an all‐day creative career workshop in the Spring 2021 semester. The five focus groups guided by semi‐structured interviews conducted for this study occurred during the workshop. This study was phenomenological in nature with constructivist and transformative paradigms, and transcripts were analyzed using reflexive thematic analysis by the first, second, and third authors. Creative adolescents' education during the pandemic was marked by classroom changes based on COVID‐19 policies, experiences of disconnection, disengagement, and disappointment, as well as feelings of empathy and appreciation for their educators. Creative adolescents experienced mental health challenges related to adjustment issues, powerlessness and hopelessness, and isolation. Implications of results are discussed. Practitioner points: Creative adolescents' education was negatively impacted by the pandemic, but they experienced empathy and appreciation for their educators Creative adolescents experienced adjustment issues, powerlessness, hopelessness, and isolation amid COVID‐19 Results suggested potential risk and protective factors in adolescent mental health and educational experiences